Two Cases of Successful Treatment With Hachimijiogan for Irregular Menstruation - Hirabayashi, Tatsuji (Frontiers in Nutrition, 2020)
Hachimijiogan (HJG), a Kampo prescription medication composed of 8 crude drugs, has been used for treatment of climacteric disturbance and irregular menstruation. In the Japanese pharmaceutical market, HJG pills consisting of powdered mixture of these crude drugs are available, as well as a water extract preparation. In this study, 2 cases of successful treatment cases with HJG pills are reported, Case 1 was a 37-year-old woman who had irregular menstruation that had been previously been treated with HJG extract granules for 3 months; however, her symptoms were not improved. Subsequent treatment with HJG pills at a dose of 40 pills/day for 10 months led to slight improvement of her menstrual cycle, and at a dose of 60 pills/day, her menstrual cycle was normalized. Case 2 was a 29-year-old woman who had irregular menstruation for more than 5 years and was previously treated with HJG extract granules, which led to slight improvement of her symptoms. Her menstrual cycle improved slightly after 9-month treatment with HJG pills at a dose of 40 pills/day and was normalized at a dose of 60 pills/day. This study suggests that the HJG crude drug preparation is more effective than the HJG extract preparation in some cases.